Territoriality in the production of adobe. Materials, alliances and mobilities in the Quebrada de Humahuaca (Huellas, 2022)
Considering territoriality in relation to adobe production in the Quebrada de Humahuaca implies analyzing the way in which people and materials are articulated in networks of relationships. In this way, the aim is to analyze the territorial dimension involved in the making of rough stones in the villages of the middle zone of the Quebrada, where the producers make use of the spaces for both extraction and elaboration. This works applies an ethnographic methodology with field work, participant observation and semi-structured interviews to raw materials producers and suppliers all along the Quebrada. It is presented in two different sections, the first one is an analysis of the dynamics within historical and contemporary domestic productions, followed by a second section in relation to the new territorialities with the expansion of the networks of relationships linked to the commercialization of adobe. This will allow us to observe how the territorialities of adobe production have been shaped hand in hand with the emergence of new socio-technical bonds, without this implying an abandonment of relationships on a domestic scale.
Keywords: territory; earth construction; techniques; social relations